2005
DOI: 10.2177/jsci.28.349
|View full text |Cite
|
Sign up to set email alerts
|

A case of Mikulicz's disease complicated by autoimmune pancreatitis, in which impaired glucose tolerance was improved by glucocorticoid treatment

Abstract: summaryA 73-year-old woman had experienced dry mouth and swellings of both upper eyelids from 1998. In October 2003, she also developed bilateral submandibular swellings, and was diagnosed with diabetes mellitus and prescribed antidiabetic medication. She consulted our hospital in the summer of 2004 due to the exacerbation of eyelid swelling, and was admitted in October 2004. Keratoconjunctivitis sicca was not present. CT and MRI of the head showed bilateral enlargement of the lacrimal and submandibular glands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Furthermore, AIP is sometimes complicated by MD. 10 , 40 Thus, MD and AIP are considered to be related. Nakamura et al reported an AIP case in which IgG4-positive mononuclear cell infiltration was observed not only in the pancreas but also in the salivary gland and kidney.…”
Section: Controversial Points Regarding Mikulicz's Diseasementioning
confidence: 99%
“…Furthermore, AIP is sometimes complicated by MD. 10 , 40 Thus, MD and AIP are considered to be related. Nakamura et al reported an AIP case in which IgG4-positive mononuclear cell infiltration was observed not only in the pancreas but also in the salivary gland and kidney.…”
Section: Controversial Points Regarding Mikulicz's Diseasementioning
confidence: 99%
“…These characteristics are similar to those of MD, i.e., elevated concentrations of serum IgG4, infiltration of IgG4-bearing plasma cells into the glands, and recovery of secretion by glucocorticoid treatment. Furthermore, AIP is sometimes complicated by MD 10,40. Thus, MD and AIP are considered to be related.…”
Section: Controversial Points Regarding Mikulicz's Diseasementioning
confidence: 99%
“…In previous reports, mPSL pulse therapy and/or moderate to high-dose corticosteroid therapy were used. [12][13][14][15][16][17] in SS complicated with interstitial nephritis. This case had severe inflammatory infiltrates in the tubulointerstitium, hypocomplementemia, positive immune complex, and elevation of sIL-2R.…”
Section: Discussionmentioning
confidence: 99%